Profiling of primary and phytonutrients in edible mahlab cherry (Prunus mahaleb L.) seeds in the context of its different cultivars and roasting as analyzed using molecular networking and chemometric tools - Mayy M. Mostafa; Mohamed A. Farag (PeerJ, 2023)
Prunus mahaleb L. (mahlab cherry) is a deciduous plant that is native to the Mediterranean region and central Europe with a myriad of medicinal, culinary and cosmetic uses. The present study explored different cultivars of mahlab (white from Egypt and Greece, red from Egypt and post roasting). UPLC-MS led to the detection of 110 primary and secondary metabolites belonging to different classes including phenylpropanoids (hydroxy cinnamates, coumaroyl derivatives), organic acids, coumarins, cyanogenic glycosides, flavonoids, nitrogenous compounds, amino acids and fatty acids, of which 39 are first time to be detected in Prunus mahaleb L. A holistic assessment of metabolites was performed for further analysis of dataset using principal component analysis (PCA) among mahlab cultivars to assess variance within seeds. The results revealed that phenolic acids (coumaric acid-O-hexoside, ferulic acid-O-hexoside, ferulic acid-O-hexoside dimer, dihydrocoumaroyl-O-hexoside dimer and ferulic acid), coumarins (coumarin and herniarin) and amino acids (pyroglutamic acid) were abundant in white mahlab cultivars (cvs.) from different locations. In contrast, red mahlab and its roasted seeds were more rich in organic acids (citric and malic acids), amygdalin derivative and sphingolipids. Orthogonal projections to latent structures discriminant analysis (OPLS-DA) revealed for markers in red mahlab and in response to roasting, where red mahlab was rich in nitrogenous compounds viz. nonamide, deoxy fructosyl leucine, glutaryl carnitine and isoleucine, while roasted product (REM) was found to be enriched in choline.